Advancement in Novel Drug Delivery System: Niosomes - Sharma, Rajni; Dua, Jagdeep Singh; Prasad, D.N.; Hira, Shabnam; Monika (Journal of Drug Delivery and Therapeutics, 2019)
Niosomes represent a promising drug delivery module. Noisome same as to liposome and Noisome represent alternative vesicular drug delivery systems with respect to liposomes, due to the noisome ability to encapsulate the different type of drugs within their multi environmental structure. Niosomes are thoughts to be a better system for drug delivery as compared to liposomes due to various factors like cost, stability etc. They are many types of drug deliveries that can be possible using niosomes like targeting, ophthalmic, topical, parenteral, etc. In recent research, comprehensive research carried over noisome as a drug carrier. Various drugs are enlisted and tried in noisome surfactant vesicles. Niosomes proved to better drug carrier system and has the potential to reduce the side effects of drugs and increased therapeutic effectiveness in various diseases. Noisome used more than fifty drugs are tried in niosomal formulations by the intravenous route, per oral administration, trans-dermal route of administration, and inhalation preparation, ocular nasal route of administration. Treatment of infectious diseases and immunization has undergone a revolutionary work in recent years. The large numbers of disease-specific biological have been developed, and also emphasis has been made to effectively deliver these biological. Niosomes shows an emerging class of novel vesicular systems. Niosomes are self-assembled vesicles composed primarily of synthetic surfactant and cholesterol. Comprehensive research carried over noisome as a drug carrier. Various drugs are enlisted and tried in noisome surfactant vesicles. This article presents an overview of the techniques of preparation of noisome, types of noisome, characterization and their applications. Keywords-Niosomes; Method of preparation; Evaluation study; Application of Niosomes